Optimization of Antioxidant Extraction from Mutisia friesiana, Native Plant of the Quebrada and Puna Regions of Argentina = Optimización de la extracción de antioxidantes de Mutisia friesiana, una planta nativa de las regiones de Quebrada y Puna de Argentina - Godoy, Mónica Daniela (2026)
The study determined the optimal conditions for extracting antioxidant phenols from Mutisia friesiana (Asteraceae) using ultrasound-assisted extraction. We evaluated extraction time, ethanol concentration, and solid/solvent ratio, applying a Box-Behnken experimental design. Response variables were total phenolic content (TPC), DPPH free radical scavenging activity (EC50), and ferric reducing antioxidant power (FRAP). All extraction variables were optimized by the response surface methodology. The optimal conditions resulted in 15 minutes of extraction, 65% ethanol, and a solid/solvent ratio of 5 g/100 mL. Under these conditions, TPC, EC50, and FRAP values were 54.24 mg GAE/g dw, 31.40 µg/mL, and 965.32 µmol EFe(II)/g dw, respectively. Extract HPLC–MS analysis under optimal conditions identified four phenolic compounds, previously reported for their antioxidant properties. This study provides valuable insights into optimal extraction parameters of bioactive compounds from M. friesiana, positioning the species as a promising natural antioxidants source for the food industry, particularly meat products.